Phylogenetic review of the tribal system of Aleocharinae, a mega‐lineage of terrestrial arthropods in need of reclassification. (14th September 2021) - Orlov, Igor; Newton, Alfred F.; Solodovnikov, Alexey
Abstract: Recently published molecular and total evidence phylogenies of the mega‐diverse rove beetle subfamily Aleocharinae defined a backbone for the greatly needed further detailed phylogenetic research and large‐scale reclassification of this lineage. Given the enormous species diversity of Aleocharinae, wise taxon sampling is crucial for such research. To facilitate that and place future systematic investigations on a solid phylogenetic basis, here we provide a review of all 62 current tribes of Aleocharinae based on information from 191 references, where we summarize all outstanding phylogenetic questions ever considered about each tribe. For each tribe, we provide current diagnoses as they are understood now and, where possible, we stress emerging monophyletic clades within or across the current legacy tribes and provide their diagnostic features too. Abstract : We provided a review of all outstanding phylogenetic questions ever considered for each of 62 current tribes of Aleocharinae rove beetles. For each tribe we provided current diagnoses as they are understood now and, where possible, we stressed emerging monophyletic clades within or across the current legacy tribes and gave their diagnostic features too. Our review will facilitate further detailed phylogenetic research and large‐scale reclassification of this enormously diverse, abundant, and scientifically challenging arthropod lineage.